2021
DOI: 10.1136/annrheumdis-2021-220702
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a patient-reported outcome measure for systemic sclerosis: the EULAR Systemic Sclerosis Impact of Disease (ScleroID) questionnaire

Abstract: ObjectivesPatient-reported outcome measures (PROMs) are important for clinical practice and research. Given the high unmet need, our aim was to develop a comprehensive PROM for systemic sclerosis (SSc), jointly with patient experts.MethodsThis European Alliance of Associations for Rheumatology (EULAR)-endorsed project involved 11 European SSc centres. Relevant health dimensions were chosen and prioritised by patients. The resulting Systemic Sclerosis Impact of Disease (ScleroID) questionnaire was subsequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 42 publications
(45 reference statements)
4
13
0
Order By: Relevance
“…The validation study showed a better sensitivity to change over a mean follow-up of 12.2 months than comparators such as Short Form-36 (SF-36), EuroQol Five Dimensional (EQ-5D), and the SSc-Health Assessment Questionnaire (HAQ). The ScleroID questionnaire proved easy to apply, had high internal consistency, and showed good correlation with the patient global assessment (109).…”
Section: Patient-reported Outcomes (Pros)mentioning
confidence: 97%
See 1 more Smart Citation
“…The validation study showed a better sensitivity to change over a mean follow-up of 12.2 months than comparators such as Short Form-36 (SF-36), EuroQol Five Dimensional (EQ-5D), and the SSc-Health Assessment Questionnaire (HAQ). The ScleroID questionnaire proved easy to apply, had high internal consistency, and showed good correlation with the patient global assessment (109).…”
Section: Patient-reported Outcomes (Pros)mentioning
confidence: 97%
“…• The ScleroID questionnaire is a new, SSc-specific, and patient-derived PRO measure which has proven superior to comparators and is thus suitable for clinical use (109).…”
Section: Take Home Messagesmentioning
confidence: 99%
“…Supported by the Programme Hospitalier de Recherche Clinique National (Ministry of Health grant PHRC P170904J). and pain are the highest patient-reported disease impacts of SSc-RP (3); however, treatment is challenging and considered an unmet clinical need by patients (3)(4)(5)(6). Patients are commonly told to avoid RP triggers, such as cold exposure, tobacco, and stress.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, SSc‐associated RP (SSc‐RP) may appear several years before systemic manifestations and can be further complicated by permanent chronic digital ischemia, including ulceration and necrosis (1,2). Impaired hand function and pain are the highest patient‐reported disease impacts of SSc‐RP (3); however, treatment is challenging and considered an unmet clinical need by patients (3–6). Patients are commonly told to avoid RP triggers, such as cold exposure, tobacco, and stress.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the limitations of the face and content validity of the MSS require an appraisal of how best to assess overall disease burden in SSc (Table 1). This question of assessing overall disease burden has recently been addressed by a team of European Alliance of Associations for Rheumatology (EULAR) researchers who have developed the EULAR Systemic Sclerosis Impact of Disease (ScleroID) questionnaire [22 ▪▪ ].…”
Section: Measuring Systemic Sclerosis Disease Severity – the Medsger ...mentioning
confidence: 99%